6.1k views
0 votes
If g(x)*x+1/x-2 abd h(x)=4-x, what is the value of (g*h) (-3)

1 Answer

4 votes

Answer:

The value of (g*h) (-3) is
=-(112)/(3)

Step-by-step explanation:

If
g(x) = x+(1)/(x)-2 and
h(x)=4-x

We have to find (g*h) (-3)

First multiply g(x) with f(x)


(x+(1)/(x)-2)* (4-x)


Distribute\:parentheses


=x\cdot \:4+x\left(-x\right)+(1)/(x)\cdot \:4+(1)/(x)\left(-x\right)+\left(-2\right)\cdot \:4+\left(-2\right)\left(-x\right)


\mathrm{Apply\:minus-plus\:rules}


+\left(-a\right)=-a,\:\:\left(-a\right)\left(-b\right)=ab


=4x-xx+4\cdot (1)/(x)-(1)/(x)x-2\cdot \:4+2x

simplify


=-x^2+6x+(4)/(x)-9

Now, put x= -3 in above expression


=-(-3)^2+6(-3)+(4)/(-3)-9


=\left(-(1)/(3)-3-2\right)\left(4+3\right)


=\left(-(16)/(3)\right)\left(4+3\right)


=7\left(-(16)/(3)\right)


=-(16)/(3)\cdot \:7


=-(112)/(3)

Therefore, the value of (g*h) (-3) is
-(112)/(3)

User Mithilesh Izardar
by
5.4k points